A spoonful of sugar: human exposure to microplastics through consumption of processed sugarcane - Jamila Patterson; K. Immaculate Jeyasanta; M. Narmatha Sathish; Andy M. Booth; V. Glen Esmeralda; R. L. Laju (Food Additives & Contaminants: Part A, 2026)

Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Meeting report: 11th international symposium on testate amoebae (ISTA-11 Niagara), Brock University, Canada, June 22–27, 2025 - Francine M.G. McCarthy; R. Timothy Patterson; Florin Pendea (Protist, 2026)

Acorn woodpeckers alter resource use, group size, and spring productivity across an urban landscape - Olivia R. Knapp; Kendra E. Forster; Alexander J. Rurik; Isabelle Hugoniot; Eric S. Reyes; Peter B. Schramm; Corban A. Muthiah; Aaron Wong; Seth C. Wilmoth; Sophia L. McRae; Caleb Courson; Theodore J. Patterson; et al. (Urban Ecosystems, 2026)
Access to suitable resources shapes the evolution and maintenance of avian cooperative breeding by influencing whether an individual will have a greater chance of survival and reproduction by dispersing or remaining on a natal territory. Cooperatively-breeding species exhibit altered dispersal according to food availability and habitat quality, but the relationship between resource use, group size, and reproduction in human-altered landscapes remains to be studied. We examined how urbanization, key resource availability, and resource use relate to differences in group size and number of offspring in an urban population of facultative cooperatively-breeding acorn woodpeckers. Acorn woodpeckers shifted to increased use of ornamental trees, palms, and anthropogenic structures for granaries in more urbanized areas and where oak trees, a key historic food and granary resource, are in lower abundance and proximity. Pair breeding was more prevalent in urbanized areas and seemed to be primarily associated with use of utility poles for granaries. In general, territories with utility poles as granaries and higher urbanization levels hosted smaller group sizes. In contrast, while the number of fledglings was higher in larger groups, it did not vary with urban resources when controlling for group size. Our findings suggest that land conversion levels and the relative availability of historic and novel resources shape habitat quality, resulting in differing patterns of group living and subsequent productivity across the urban landscape. This indicates that while novel resources may enable wildlife to occupy urban areas, they may also influence the social behavior of facultative cooperative breeders.

Including Fitness and Health Proxies Can Alter Our Understanding of Habitat Selection - Marie Auger‐Méthé; Fanny Dupont; Alyssa Eby; Kyle H. Elliott; Nigel E. Hussey; Devin A. Lyons; Marianne Marcoux; Allison Patterson; Shabnam Shadloo; Courtney R. Shuert (Ecology Letters, 2026)
Habitat selection analyses, which discern the environmental conditions individuals select, often inform conservation planning. Through a literature review, we demonstrate that recent habitat selection studies rarely include fitness and health information. With a simulation study, we show that ignoring such information could support the protection of sink habitats. Our case studies demonstrate how health and fitness proxies can modify our understanding of habitat selection: (1) incorporating mass gain of thick‐billed murres shows the energetic benefit of areas deemed secondary by a naive resource selection function; (2) including number of chicks in a step selection function (SSF) exposes the complex relationships glaucous‐winged gulls have with landscapes impacted by humans; and (3) including external signs of trauma in the movement kernel of SSFs demonstrates other ways in which narwhal distribution can be altered. We urge movement ecologists to collect and use health and fitness data to improve ecological inference and conservation action.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Arbuscular Mycorrhizal Fungi Colonise the Nodules of Phosphite‐Treated Agathis australis - Haileigh R. Patterson; Andrew Dopheide; Duckchul Park; Luitgard Schwendenmann; Mahajabeen Padamsee (New Zealand Journal of Botany, 2026)
Agathis australis (kauri), the only member of the ancient conifer family Araucariaceae in New Zealand, is colonised by arbuscular mycorrhizal (AM) fungi. The survival of A. australis is threatened by an Oomycota, Phytophthora agathidicida , the causal agent of kauri dieback. Phosphite injections into the trunk are the primary treatment for kauri dieback and have proven effective in reducing disease symptoms. However, the potential impact of phosphite treatment on AM fungal colonisation within A. australis roots and nodules has not been investigated. We conducted a preliminary investigation into whether AM fungi colonise phosphite‐treated trees. Using a combination of microscopy and metabarcoding of AM fungi 18S nuclear ribosomal small subunit genes, we demonstrate that AM fungi colonise the roots and nodules of A. australis trees three to 4 years post‐treatment. Glomeraceae was found to dominate, and AM fungi community composition and colonisation rates were comparable to previously reported values in trees not treated with phosphite. Soil pH, but not date of phosphite treatment or PA infection status, was found to significantly contribute to AM fungal community composition. This work highlights the importance in investigating colonisation events immediately after phosphite treatment of A. australis and a comparison with untreated trees. AM fungi are likely integral for A. australis forests to thrive, thus, ensuring they are protected in the treatment of kauri dieback is essential.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Bomb radiocarbon reveals keratin growth dynamics in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles - Bethan Linscott; Amy A. Wallace; Lorena Becerra-Valdivia; Matt R. P. Harris; Alexandra L. Fireman; Jenna D. Bennett; William F. Patterson; Hannah B. Vander Zanden (Marine Biology, 2026)
Incrementally formed biological tissues can serve as archives of biochemical information pertaining to the life histories of organisms. The sequential isotopic analysis of marine turtle scute keratin is increasingly used for ecological reconstruction, but the timescales represented by these tissues remain poorly understood. Here, we present a method to establish scute growth rates using sequential radiocarbon ( 14 C) measurements on samples taken from loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) stranded along the Florida coast. Using a Δ 14 C coral-otolith reference series and a Bayesian modelling approach, we reconstructed the rate of keratin formation in 24 individuals (representing 120 radiocarbon measurements) and detected synchronous declines in scute growth rates that may be linked to marine environmental stress. Our results provide a chronological framework for the ecological interpretation of biogeochemical data from green and loggerhead turtle scutes and demonstrate the potential for 14 C analysis to investigate the growth dynamics of other incremental tissues.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Quantifying changes in central Vietnam rainfall amount since the Late Pleistocene - Elizabeth W. Patterson; Alliya A. Akhtar; Michael L. Griffiths; David McGee; Quốc Đỗ-Trọng; Annabel Wolf; John A. Higgins; Stefania Gili; Mùi X. Trần; Hùng Q. Nguyễn; Trí H. Đinh; Thành N. Bùi; et al. (Earth and Planetary Science Letters, 2026)

Multi‐Decadal Changes in Co‐Occurrence of Migrating Landbirds Are Associated With Species‐Specific Changes in Phenology and Abundance - Joely G. DeSimone; Evan Dalton; Lucas W. DeGroote; Matthew Fuirst; Sara R. Morris; Andrea J. Patterson; Emily B. Cohen (Global Change Biology, 2025)
Human‐induced changes to the climate and environment have precipitated dramatic declines in abundance and shifts in plant and animal phenologies. These changes have been especially pronounced for migratory species that rely on numerous geographic locations throughout the year. Migratory bird species are notable in the number of species that have experienced both declines in abundance and shifts in phenology over the past 50 years, although the magnitude and direction of changes vary considerably across species. The community‐level impacts of species declines and phenological shifts have been explored in stationary communities, but we know little about the effects of these changes on species relationships during migration seasons when species may interact in ways that influence their route, timing, or success of the journey (e.g., through competition or access to information about resources). Therefore, we assessed the extent to which co‐migrating bird communities have changed over time, and whether changes in species co‐occurrence are associated with changes in abundance or shifts in migration timing. We used over 700,000 records of birds captured at five long‐term migration monitoring stations in eastern North America and found that pairwise species co‐occurrences have changed by as much as 40% over the past 50 years. Changes in co‐occurrence were consistently associated with species‐specific changes in phenology and sometimes associated with changes in abundance. Overall, stopover communities at three sites have significantly changed over the past few decades. Numerous and dramatic changes in co‐occurrence could be affecting the types and frequencies of interspecific interactions like competition and the exchange of social information, transforming the journeys of migratory birds in innumerable ways that could be altering their timing, energy, and safety.

Habitat selection as a reduction in habitat variance - Jenna Knight; James A. Schaefer; Brent R. Patterson; Stephen Sucharzewski; Joseph M. Northrup (Acta Oecologica, 2025)

Birds of a Feather Self-Regulate Together: The Intersection of Peer Networks and Self-Regulated Learning in Biomedical Engineering - Linlin Luo; Joseph C. Tise; Megan S. Patterson; Daniel L. Alge; Paul R. Hernandez (Biomedical Engineering Education, 2025)

Opportunity Knocks: Leveraging Offshore Wind Development as a Natural Experiment to Address the Ecological Function of Artificial Reefs - Raymond E. Czaja; Shayna A. Sura; William F. Patterson; David D. Chagaris; John F. Walter; Skyler R. Sagarese; Avery B. Paxton; William D. Heyman; Holden E. Harris (Fish and Fisheries, 2025)
Artificial structures deployed in marine environments as reefs are often presumed to increase fish production. However, our literature review found a lack of evidence, with only 12 studies empirically quantifying secondary production at artificial reefs, and only three studies using a control site. We propose the forthcoming large‐scale construction of offshore wind (OSW) energy structures presents a natural experiment to examine the ecological function of artificial reefs, including their effects on fish production. To provide causal inferences of OSW effects, studies must obtain appropriate ‘before’ data, per before‐after‐control‐impact and related designs. This requirement dictates that society must begin planning and collecting data now, prior to OSW deployment. We also highlight that responses beyond fish biomass measures, including life stage specific survival, site fidelity and trophic dynamics, must occur at appropriate spatial and temporal scales to maximise causal inference. By leveraging a timely opportunity and natural experiment with OSW development, the long‐running ‘attraction–production debate’ about artificial reef ecological function may be addressed.

4-H youth comprehension, perceptions, and selection of tack and its implications for equine welfare - K. Irvine; C.L. Wickens; M. Nelson; R. Prasad; L.N.R. Patterson (Journal of Equine Veterinary Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Assessment of beach litter, including Abandoned, Lost, or Discarded Fishing Gear (ALDFG), along the coast of Tamil Nadu, India: Magnitude, sources, composition, pollution status, and management strategies - J.K. Patterson Edward; M. Jayanthi; Haraldur A. Einarsson; R. Kannan; R.L. Laju; K. Immaculate Jeyasanta; Narmatha Sathish; Jamila Patterson (Marine Pollution Bulletin, 2025)

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The biodiversity of ice‐free Antarctica database - Aleks Terauds; Jasmine R. Lee; Hannah S. Wauchope; Ben Raymond; Dana M. Bergstrom; Peter Convey; Claire Mason; Charlotte R. Patterson; Sharon A. Robinson; Anton Van de Putte; David Watts; Steven L. Chown (Ecology, 2025)
Antarctica is one of Earth's most untouched, inhospitable, and poorly known regions. Although knowledge of its biodiversity has increased over recent decades, a diverse, wide‐ranging, and spatially explicit compilation of the biodiversity that inhabits Antarctica's permanently ice‐free areas is unavailable. This absence hinders both Antarctic biodiversity research and the integration of Antarctica in global biodiversity–related studies. Fundamental and applied research on biodiversity patterns, ecological structure and function, and options for conservation are reliant on spatially resolved, taxonomically consistent observations. Such information is especially important for modern, data‐driven biodiversity science, in both Antarctica and globally, and forms the backbone of biodiversity informatics, reflected, for example, in the Darwin Core Standard used by the Global Biodiversity Information Facility. Biodiversity data are also essential to fulfill the conservation requirements for Antarctica, as set out in the Protocol on Environmental Protection to the Antarctic Treaty and inform the design of systematic surveys to address biodiversity and ecological knowledge gaps, for both specific taxa and ecosystems. Such surveys are key requirements for understanding and mitigating the impacts of environmental change on the region's biodiversity. Here, we address these requirements through the public release of The Biodiversity of Ice‐free Antarctica Database. In 2008, we extracted a subset of biodiversity records only from terrestrial ice‐free areas from the Scientific Committee on Antarctic Research (SCAR) Antarctic Biodiversity Database. We have subsequently added thousands of records from a range of sources: checking, and where necessary (and possible), correcting the spatial location, clarifying, cross‐referencing, and harmonizing taxonomy with globally recognized sources, and documenting the original source of records. The Biodiversity of Ice‐free Antarctica Database spans the early 1800s to 2019 (with most records collected after 1950) and represents the most comprehensive consolidation of Antarctic ice‐free biodiversity occurrence data yet compiled into a single database. The Biodiversity of Ice‐free Antarctica Database contains 35,654 records of 1890 species in over 800 genera across six kingdoms and spans all Antarctic Conservation Biogeographic Regions. These data are released under a CC BY Attribution License ( http://creativecommons.org/licenses/by/4.0/ ).

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Organic matter is a predominant control on total mercury concentration of near-surface lake sediments across a boreal to low Arctic tundra transect in northern Canada - Jennifer M. Galloway; Michael B. Parsons; Omid H. Ardakani; Hendrik Falck; Richard E. Fewster; Graeme T. Swindles; Hamed Sanei; Michael J. Palmer; Nawaf A. Nasser; R. Timothy Patterson (Science of The Total Environment, 2024)

Risk avoidance during dispersal: Temporal and behavioral shifts in selection by non-resident eastern wolves (Canis c.f. lycaon) - Connor A. Thompson; John F. Benson; Brent R. Patterson (Biological Conservation, 2024)

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

Infection prevention and control and related practices in African neonatal units: The Pan-African neonatal care assessment study (PANCAS) - Irene Frantzis; Stéphanie Levasseur; Jack Huebner; Maitry Mahida; Philip Larussa; Wilmot James; Workeabeba Abebe; Crispen Ngwenya; Ezekiel Mupere; Susan L. Rosenthal; Janna Patterson; Julia Johnson; et al. (International Journal of Hygiene and Environmental Health, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Effects of an enzyme mixture supplementation on energy and nutrient digestibility in soybean expellers fed to growing pigs - J. Song; A. Aljuobori; R. Patterson; C.M. Nyachoti (Animal Feed Science and Technology, 2024)

The effect of urbanization and behavioral factors on coyote net displacement and its implications for seed dispersal - Tiziana A. Gelmi-Candusso; Tyler J. Wheeldon; Brent R. Patterson; Marie-Josée Fortin (Urban Ecosystems, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Tidally induced fault motion within Europa's ice shell and implications for subsurface communication development - Rudi R. Lien; Kathleen L. Craft; Matthew E. Walker; G. Wesley Patterson; Alyssa R. Rhoden (Icarus, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Estimating reductions in the risk of vessels striking whales achieved by management strategies - Jessica V. Redfern; Brooke C. Hodge; Daniel E. Pendleton; Amy R. Knowlton; Jeffrey Adams; Eric M. Patterson; Caroline P. Good; Jason J. Roberts (Biological Conservation, 2024)

Quantifying conditions required for varve formation in meromictic Crawford Lake, Ontario, Canada: important process for delimiting the Anthropocene epoch - Brendan M. Llew-Williams; Francine M. G. McCarthy; Andrea M. Krueger; Nicholas L. Riddick; Michael D. MacKinnon; Krysten M. Lafond; R. Timothy Patterson; Nawaf A. Nasser; Martin J. Head; Michael F. J. Pisaric; Kevin W. Turner; Joseph I. Boyce; et al. (Journal of Paleolimnology, 2024)

Effects of urbanization on the efficiency and composition of vertebrate scavengers - Jessica R. Patterson; Nicolas Szabo; James C. Beasley (Food Webs, 2023)

Contaminated sediment in the Detroit River provokes acclimated responses in wild brown bullhead (Ameiurus nebulosus) populations - J. Assad; S. Cho; V. Dileo; G. Gascoigne; A.V. Hubberstey; D. Patterson; R. Williams (Aquatic Toxicology, 2023)

Ultraconserved elements resolve phylogenetic relationships and biogeographic history of African-Malagasy bent-winged bats (Miniopterus) - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Holly L. Lutz; Bernard R. Agwanda; Natalia Cortés-Delgado; Stefania Briones; Richard H. Ree; Bruce D. Patterson (Molecular Phylogenetics and Evolution, 2023)

Cue selection and ontogeny reveal larval settlement dynamics of the long-spined sea urchin Diadema antillarum, a keystone coral reef herbivore - Aaron R. Pilnick; Alex Petrosino; Md Mahbubul Hassan; Joshua T. Patterson (Marine Biology, 2023)

Evaluation of Zoetis GeneMax Advantage genomic predictions in commercial Bos taurus Angus cattle - Brian.C. Arisman; Troy N. Rowan; Jordan M. Thomas; Harly J. Durbin; William R. Lamberson; David J. Patterson; Jared E. Decker (Livestock Science, 2023)

Evaluating the fidelity of enamel isotopic data and environmental variation in paleoecological studies: A case study in wild, known-aged, modern white-tailed deer (Odocoileus virginianus) - Taylor Malasek; Erin Barding; Michael J. Bender; Alexandra Bonham; Alfred J. Mead; Zachary Pilgrim; Patrick Powers; Jessica R. Patterson; David B. Patterson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Forecast‐ready models to support fisheries' adaptation to global variability and change - Kylie L. Scales; Thomas S. Moore; Bernadette Sloyan; Claire M. Spillman; J. Paige Eveson; Toby A. Patterson; Ashley J. Williams; Alistair J. Hobday; Jason R. Hartog (Fisheries Oceanography, 2023)
Ocean and climate drivers affect the distribution and abundance of marine life on a global scale. Marine ecological forecasting seeks to predict how living marine resources respond to physical variability and change, enabling proactive decision‐making to support climate adaptation. However, the skill of ecological forecasts is constrained by the skill of underlying models of both ocean state and species‐environment relationships. As a test of the skill of data‐driven forecasts for fisheries, we developed predictive models of catch‐per‐unit‐effort (CPUE) of tuna and billfish across the south‐west Pacific Ocean, using a 12‐year time series of catch data and a large ensemble climate reanalysis. Descriptors of water column structure, particularly temperature at depth and upper ocean heat content, emerged as useful predictors of CPUE across species. Enhancing forecast skill over sub‐seasonal to multi‐year timescales in any system is likely to require the inclusion of sub‐surface ocean data and explicit consideration of regional physical dynamics.

Assessing the viability of CO 2 storage in offshore formations of the Gulf of Mexico at a scale relevant for climate-change mitigation - Josimar A. Silva; Lluís Saló-Salgado; Joseph Patterson; Ganeswara R. Dasari; Ruben Juanes (International Journal of Greenhouse Gas Control, 2023)

Microscale flow dynamics and particle capture in scleractinian corals: I. Role of the tentacles - Wm. Stephen Price; Mark R. Patterson (Coral Reefs, 2023)
The size, shape, and arrangement of tentacles in scleractinian coral polyps are likely to affect particle capture yet have not been investigated in a systematic way. Morphometric measurements of tentacles of several coral species found in the Caribbean Sea were taken from macro-photographs, and from these, models were constructed in three postures: straight, upstream-facing, and downstream-facing. These models were placed in a flume to video the flow paths of particles around them. Video analysis indicates tentacles, and their specific postures, have a dramatic effect on micro-flow patterns. The expanded soft tissue tentacles, and their specific postures, greatly increase probability of particle capture by direct impaction, inertial impaction, and gravitational deposition. All tentacle postures cause increased retention time relative to freestream travel in their immediate proximity, as well as increasing both contact with the tentacle surface, and tumbling of particles. Straight and upstream-facing tentacles deflect particles downward to their base, while downstream-facing tentacles deflect particles upwards. When results from individual tentacles are considered in geometric combination, the secondary radial symmetry of the tentacular whorls in simple coral polyps appears to be an optimal strategy to filter suspended particulate material in an oscillating and omni-directional flow environment. In meandrine corals, the hedgerows of straight and curved tentacles appear to draw particles downward, retain them, and direct them onto the oral feeding areas below the thecal ridges. The size, shape, and arrangement of tentacles are thus of key importance in understanding suspension feeding in scleractinian corals.

Long-term retention and density-dependent herbivory from Diadema antillarum following translocation onto a reef restoration site - Aaron R. Pilnick; Joseph A. Henry; Dalton Hesley; John L. Akins; Joshua T. Patterson; Diego Lirman (Coral Reefs, 2023)

94 Age and feeding behavior associated with dental disorders in Western horses - K.Y. Lai; N. Moore; R. Allen; H. Santos; J. Boyd; L. Patterson Rosa (Journal of Equine Veterinary Science, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Three trap designs evaluated for a deepwater lionfish fishery - Holden E. Harris; Steven B. Garner; Joseph H. Tarnecki; Stephen R. Gittings; David D. Chagaris; William F. Patterson (Frontiers in Marine Science, 2023)
A deepwater (>40 m) fishery for invasive lionfish ( Pterois volitans/miles ) offers a potential means to control invasive lionfish densities and mitigate their impacts on reefs too deep for SCUBA removals. Trapping could provide a scalable solution—if an effective fishing gear with minimal environmental impacts could be permitted and adopted by fishers. We tested the efficacy of wooden slat lobster traps, wire sea bass traps, and experimental non-containment Gittings traps. One hundred deployments of each trap type were made at 120 mesophotic (38–78 m deep) natural reef sites in the northeastern Gulf of Mexico (29.6–30.1°N, 86.1–87.6°W). Reef sites were surveyed with remotely operated vehicles (ROV) before and after trap deployments, and remote time-lapse video cameras were affixed above 86 traps to sample in situ recruitment to the traps. The video data showed that lionfish were attracted to the vicinity of the three trap types at similar rates, but that lionfish rarely entered the lobster or sea bass traps. The high bycatch rates of sea bass traps suggested their use is likely unsuitable for targeting lionfish. Lobster traps had lower rates of bycatch, but their relatively high ratio of bycatch-to-lionfish catches suggests that modifications will be needed to make them more efficient. The Gittings traps had the highest lionfish catch rates and lowest bycatches of native fishes, but operational issues were also identified. They failed to open on 20% of deployments and one entangled a green sea turtle ( Chelonia mydas ). Even with the best-performing trap design, the average catch rate of lionfish was less than one lionfish per trap. A potential explanation could be the low biomass of lionfish observed during the ROV surveys, which averaged 0.3 kg lionfish per site. The time-lapse video data suggested that lionfish recruitment to Gittings traps could increase with higher densities of lionfish on the nearby reefs, if traps were retrieved after approximately two days of deployment, and if traps were retrieved during dawn or dusk. Further research, development, and testing is needed for lionfish traps, and critical bio- and techno-economic assessments appear warranted to evaluate the feasibility of a deepwater lionfish fishery.

Hydrochemical quality and microplastic levels of the groundwaters of Tuticorin, southeast coast of India - Jamila Patterson; R. L. Laju; K. Immaculate Jeyasanta; S. Shelciya; V. Glen Esmeralda; N. Gladwin Gnana Asir; M. Narmatha; Andy M. Booth (Hydrogeology Journal, 2023)

Perceptions of Freshwater Algal Blooms, Causes and Health among New Brunswick Lakefront Property Owners - Sapriya Birk; J. David Miller; Aidan MacMullin; R. Timothy Patterson; Paul J. Villeneuve (Environmental Management, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Novel shaker bottle cultivation method for the long spined sea urchin (Diadema antillarum; Philippi, 1845) results in high larval survival and settlement rates - Tom Wijers; Alwin Hylkema; Aaron R. Pilnick; Albertinka J. Murk; Joshua T. Patterson (Aquaculture, 2023)

Development of larviculture protocols for the long-spined sea urchin (Diadema antillarum) and enhanced performance with diets containing the cryptophyte Rhodomonas lens - Aaron R. Pilnick; Keri L. O’Neil; Matthew A. DiMaggio; Joshua T. Patterson (Aquaculture International, 2022)

Impact of Post-Tropical Storm Arthur (2014) on benthic Arcellinida assemblage dynamics in Harvey Lake, New Brunswick, Canada - Dan Atasiei; Nawaf A. Nasser; Calder W. Patterson; Anqi Wen; R. Timothy Patterson; Jennifer M. Galloway; Helen M. Roe (Hydrobiologia, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

A portable extruder for accurate and precise high-resolution subsampling of unconsolidated sediment cores - R. Timothy Patterson; Nawaf A. Nasser; Steven Tremblay; Jennifer M. Galloway (Journal of Paleolimnology, 2022)

A first genetic assessment of the newly introduced Isle Royale gray wolves (Canis lupus) - Samuel D. Hervey; Linda Y. Rutledge; Brent R. Patterson; Mark C. Romanski; John A. Vucetich; Jerrold L. Belant; Dean E. Beyer; Seth A. Moore; Kristin E. Brzeski (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Strategies for integrating sexually propagated corals into Caribbean reef restoration: experimental results and considerations - Joseph A. Henry; Keri L. O’Neil; Aaron R. Pilnick; Joshua T. Patterson (Coral Reefs, 2021)

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Repeated ex situ Spawning in Two Highly Disease Susceptible Corals in the Family Meandrinidae - Keri L. O’Neil; Rachel M. Serafin; Joshua T. Patterson; Jamie R. K. Craggs (Frontiers in Marine Science, 2021)
Members of the family Meandrinidae are highly susceptible to stony coral tissue loss disease, resulting in population reductions up to 88% in both Dendrogyra cylindrus and Meandrina meandrites along the Florida Reef Tract. Reductions in abundance on this scale leave these species susceptible to limitations in sexual reproduction and natural recovery without intervention. In response to the ongoing outbreak of the disease across the Caribbean, a variety of genetic rescue projects have been implemented to bring disease susceptible species into ex situ culture and preserve living genetic diversity. In this study, corals being held in a long-term ex situ genetic bank were maintained using artificial lighting and temperature cues programmed to mimic natural cycles in Key Largo, FL, United States. Synchronized broadcast spawning events in both species were documented in aquaria over two annual spawning cycles in 2019 and 2020. Timing of gamete release relative to the perceived date and sunset was highly synchronized with wild observations. Up to 21 unique D. cylindrus genotypes collected from reef locations spanning over 230 km contributed gametes to the larval pool. The majority of these parental colonies are no longer alive in the wild. Repeatable and predictable ex situ spawning events such as these will become an essential tool for managed breeding and assisted fertilization in species suffering from severe population declines. These annual events have the potential to produce thousands of genetically diverse offspring for restoration efforts and offer future hope for the long-term survival of these threatened species.

Determining effective acoustic array design for monitoring presence of white sharks Carcharodon carcharias in nearshore habitats - Sofia M. Gabriel; T. A. Patterson; J. P. Eveson; J. M. Semmens; D. Harasti; P. A. Butcher; J. L. Y. Spaet; R. W. Bradford (Marine Biology, 2021)

Environmental Influences on Long-term Movement Patterns of a Euryhaline Elasmobranch (Carcharhinus leucas) Within a Subtropical Estuary - R. D. Pillans; G. C. Fry; A. D. L. Steven; T. Patterson (Estuaries and Coasts, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Coming to Terms With Living Shorelines: A Scoping Review of Novel Restoration Strategies for Shoreline Protection - Carter S. Smith; Morgan E. Rudd; Rachel K. Gittman; Emily C. Melvin; Virginia S. Patterson; Julianna J. Renzi; Emory H. Wellman; Brian R. Silliman (Frontiers in Marine Science, 2020)

Resistance and robustness of the global coral–symbiont network - Sara D. Williams; Mark R. Patterson (Ecology, 2020)
Increasing ocean temperatures have widespread consequences for coral reefs, one of which is coral bleaching. We analyzed a global network of associations between coral species and Symbiodiniaceae for resistance to temperature stress and robustness to perturbations. Null networks were created by changing either the physiological parameters of the nodes or the structures of the networks. We developed a bleaching model in which each link, association, is given a weight based on temperature thresholds for specific host–symbiont pairs and links are removed as temperature increases. Resistance to temperature stress was determined from the response of the networks to the bleaching model. Ecological robustness, defined by how much perturbation is needed to decrease the number of nodes by 50%, was determined for multiple removal models that considered traits of the hosts, symbionts, and their associations. Network resistance to bleaching and robustness to perturbations differed from the null networks and varied across spatial scales, supporting that thermal tolerances, local association patterns, and environment play an important role in network persistence. Networks were more robust to attacks on associations than to attacks on species. Although the global network was fairly robust to random link removals, when links are removed according to the bleaching model, robustness decreases by about 20%. Specific environmental attacks, in the form of increasing temperatures, destabilize the global network of coral species and Symbiodiniaceae. On a global scale, the network was more robust to removals of links with susceptible Symbiodiniaceae than it was to removals of links with susceptible hosts. Thus, the symbionts convey more stability to the symbiosis than the hosts when the system is under an environmental attack. However, our results also provide evidence that the environment of the networks affects robustness to link perturbations. Our work shows that ecological resistance and robustness can be assessed through network analysis that considers specific biological traits and functional weaknesses. The global network of associations between corals and Symbiodiniaceae and its distribution of thermal tolerances are non‐random, and the evolution of this architecture has led to higher sensitivity to environmental perturbations.

Response to comment: ischemic preconditioning and exercise performance: shedding light through smallest worthwhile - Moacir Marocolo; Mario A. Moura Simim; Anderson Bernanrdino; Iury Reis Monteiro; Stephen Patterson; Gustavo R. Mota (European Journal of Applied Physiology, 2020)

Selective Regulation of 5-HT1B Serotonin Receptor Expression in the Striatum by Dopamine Depletion and Repeated L-DOPA Treatment: Relationship to L-DOPA-Induced Dyskinesias - Fernando E. Padovan-Neto; Santanna Patterson; Nivea M. F. Voelkner; Feras Altwal; Joel A. Beverley; Anthony R. West; Heinz Steiner (Molecular Neurobiology, 2020)

NASA’s satellite laser ranging systems for the twenty-first century - J. F. McGarry; E. D. Hoffman; J. J. Degnan; J. W. Cheek; C. B. Clarke; I. F. Diegel; H. L. Donovan; J. E. Horvath; M. Marzouk; A. R. Nelson; D. S. Patterson; R. L. Ricklefs; et al. (Journal of Geodesy, 2019)

Ischemic preconditioning and exercise performance: shedding light through smallest worthwhile change - Moacir Marocolo; Mario A. Moura Simim; Anderson Bernardino; Iury Reis Monteiro; Stephen D. Patterson; Gustavo R. da Mota (European Journal of Applied Physiology, 2019)

Movement responses to environment: fast inference of variation among southern elephant seals with a mixed effects model - I. D. Jonsen; C. R. McMahon; T. A. Patterson; M. Auger‐Méthé; R. Harcourt; M. A. Hindell; S. Bestley (Ecology, 2019)
Like many species, movement patterns of southern elephant seals ( Mirounga leonina ) are being influenced by long‐term environmental change. These seals migrate up to 4,000 km from their breeding colonies, foraging for months in a variety of Southern Ocean habitats. Understanding how movement patterns vary with environmental features and how these relationships differ among individuals employing different foraging strategies can provide insight into foraging performance at a population level. We apply new fast‐estimation tools to fit mixed effects within a random walk movement model, rapidly inferring among‐individual variability in southern elephant seal environment–movement relationships. We found that seals making foraging trips to the sea ice on or near the Antarctic continental shelf consistently reduced speed and directionality (move persistence) with increasing sea‐ice coverage but had variable responses to chlorophyll a concentration, whereas seals foraging in the open ocean reduced move persistence in regions where circumpolar deep water shoaled. Given future climate scenarios, open‐ocean foragers may encounter more productive habitat but sea‐ice foragers may see reduced habitat availability. Our approach is scalable to large telemetry data sets and allows flexible combinations of mixed effects to be evaluated via model selection, thereby illuminating the ecological context of animal movements that underlie habitat usage.

Genotyping confirms significant cannibalism in northern Gulf of Mexico invasive red lionfish, Pterois volitans - Kristen A. Dahl; David S. Portnoy; J. Derek Hogan; John E. Johnson; John R. Gold; William F. Patterson (Biological Invasions, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Factors affecting estimates of size at age and growth in grey triggerfish Balistes capriscus from the northern Gulf of Mexico - R. J. Allman; W. F. Patterson; C. L. Fioramonti; A. E. Pacicco (Journal of Fish Biology, 2018)
Growth zones in dorsal spines of grey triggerfish Balistes capriscus from the northern Gulf of Mexico were utilized to estimate growth and examine factors that may affect estimates of size at age. Age was estimated from dorsal‐spine sections of 4687 individuals sampled from U.S. waters during 2003–2013, including both fishery‐independent ( n = 1312) and fishery‐dependent ( n = 3375) samples. Ninety‐six per cent ( n = 4498) of these sections were deemed suitable for ageing; average per cent error between two independent readers was 10·8%. Fork length ( L F ) ranged from 65 to 697 mm and age estimates from 0 to 14 years. Both sex and sample source (fishery‐independent v . recreational) significantly affected estimated size at age for 2–6 year‐old fish. Data were pooled between sources to fit sex‐specific von Bertalanffy growth functions. Results for the female model were L ∞ = 387 mm L F , k = 0·52 year −1 and t 0 = 0·01 year, while for males L ∞ = 405 mm L F , k = 0·55 year −1 and t 0 = 0·02 year. These results were significantly different between sexes and indicate clear sexual dimorphism. Thus, growth should be modelled separately by sex when examining population parameters or conducting stock assessment modelling. The positive bias in estimates of size at age computed for recreational v . fishery‐independent samples also has clear implications for stock assessment as growth functions computed with fishery‐dependent samples would tend to overestimate stock productivity.

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Hydrology of the North Klondike River: carbon export, water balance and inter-annual climate influences within a sub-alpine permafrost catchment - Anthony Lapp; Ian D. Clark; Andrew L. Macumber; R. Timothy Patterson (Isotopes in Environmental and Health Studies, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Novel mutations involving βI-, βIIA-, or βIVB-tubulin isotypes with functional resemblance to βIII-tubulin in breast cancer - Weiwei Wang; Hangxiao Zhang; Xumin Wang; Jordan Patterson; Philip Winter; Kathryn Graham; Sunita Ghosh; John C. Lee; Christos D. Katsetos; John R. Mackey; Jack A. Tuszynski; Gane Ka-Shu Wong; et al. (Protoplasma, 2017)

Sequential sample reservoirs for Itrax-XRF analysis of discrete samples - Braden R. B. Gregory; Eduard G. Reinhardt; Andrew L. Macumber; Nawaf A. Nasser; R. Timothy Patterson; Shawn E. Kovacs; Jennifer M. Galloway (Journal of Paleolimnology, 2017)

Mesophotic Coral Ecosystems: A Geoacoustically Derived Proxy for Habitat and Relative Diversity for the Leeward Shelf of Bonaire, Dutch Caribbean - Arthur C. Trembanis; Alexander L. Forrest; Bryan M. Keller; Mark R. Patterson (Frontiers in Marine Science, 2017)

Shrinking of Vann Island, Gulf of Mannar, SE coast of India: assessing the impacts - M. Jayaprakash; K. Sivakumar; S. Muthusamy; R. R. Krishnamurthy; J. K. Edward Patterson (Natural Hazards, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Erratum to: Influence of ocean–atmospheric oscillations on lake ice phenology in eastern North America - R. Timothy Patterson; Graeme T. Swindles (Climate Dynamics, 2015)

Influence of ocean–atmospheric oscillations on lake ice phenology in eastern North America - R. Timothy Patterson; Graeme T. Swindles (Climate Dynamics, 2015)

Thermal regime, predation danger and the early marine exit of sockeye salmon Oncorhynchus nerka - P. J. Katinic; D. A. Patterson; R. C. Ydenberg (Journal of Fish Biology, 2015)
Marine exit timing of sockeye salmon Oncorhynchus nerka populations on the Haida Gwaii Archipelago, British Columbia, Canada, is described, with specific focus on Copper Creek. Marine exit in Copper Creek occurs > 130 days prior to spawning, one of the longest adult freshwater residence periods recorded for any O. nerka population. Copper Creek presents an easy upstream migration, with mild water temperatures (7 to 14° C), short distance (13·1 km) and low elevation gain (41 m) to the lake where fish hold prior to spawning. An energetic model estimates that O.nerka streams in Haida Gwaii has ever exceeded the presumed temperature threshold (19° C) for early marine exit. Although it is not impossible that the thermal tolerance of Copper Creek O.nerka is very low, the data presented here appear inconsistent with thermal avoidance as an explanation for the early marine exit timing in Copper Creek and in three other populations on the archipelago with early marine exit.

Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada - Lindsay M. Upiter; Jesse C. Vermaire; R. Timothy Patterson; Carley A. Crann; Jennifer M. Galloway; Andrew L. Macumber; Lisa A. Neville; Graeme T. Swindles; Hendrik Falck; Helen M. Roe; Michael F. J. Pisaric (Journal of Paleolimnology, 2014)

A protected area influences genotype‐specific survival and the structure of a Canis hybrid zone - John F. Benson; Brent R. Patterson; Peter J. Mahoney (Ecology, 2014)
It is widely recognized that protected areas can strongly influence ecological systems and that hybridization is an important conservation issue. However, previous studies have not explicitly considered the influence of protected areas on hybridization dynamics. Eastern wolves are a species of special concern and their distribution is largely restricted to a protected population in Algonquin Provincial Park (APP), Ontario, Canada, where they are the numerically dominant canid. We studied intrinsic and extrinsic factors influencing survival and cause‐specific mortality of hybrid and parental canids in the three‐species hybrid zone between eastern wolves, eastern coyotes, and gray wolves in and adjacent to APP. Mortality risk for eastern wolves in areas adjacent to APP was significantly higher than for other sympatric Canis types outside of APP, and for eastern wolves and other canids within APP. Outside of APP, the annual mortality rate of all canids by harvest (24%) was higher than for other causes of death (4–7%). Furthermore, eastern wolves (hazard ratio = 3.5) and nonresidents (transients and dispersing animals, hazard ratio = 2.7) were more likely to die from harvest relative to other Canis types and residents, respectively. Thus, eastern wolves dispersing from APP were especially vulnerable to harvest mortality. For residents, eastern wolf survival was more negatively influenced by increased road density than for other Canis types, further highlighting the sensitivity of eastern wolves to human disturbance. A cycle of dispersal from APP followed by high rates of mortality and hybridization appears to maintain eastern wolves at low density adjacent to APP, limiting the potential for expansion beyond the protected area. However, high survival and numerical dominance of eastern wolves within APP suggest that protected areas can allow rare hybridizing species to persist even if their demographic performance is compromised and barriers to hybridization are largely absent in the adjacent matrix.

Inter-specific territoriality in a Canis hybrid zone: spatial segregation between wolves, coyotes, and hybrids - John F. Benson; Brent R. Patterson (Oecologia, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Using PET / CT imaging to characterize 18 F‐fluorodeoxyglucose utilization in fish - Z S Browning; A A Wilkes; D S MacKenzie; R M Patterson; M W Lenox (Journal of Fish Diseases, 2013)
Fish are becoming an increasingly important research species as investigators seek alternatives to mammalian models. Combined positron emission tomography/computed tomography with 18 F‐fluorodeoxyglucose ( FDG ‐ PET / CT ) is a powerful new technology that has been extensively applied for high‐resolution imaging in mammals but not fish. CT scanning provides detailed anatomical three‐dimensional imaging. PET scanning detects areas of cellular activity using radio‐labelled molecular probes with specific uptake rates appropriate to the tissue involved. FDG ‐ PET is used in oncology because tissues with high glucose uptake, such as neoplasms, are intensely radio‐labelled. PET / CT combines the two technologies, so that images acquired from both devices are merged into one superimposed image, thus more precisely correlating metabolic activity with anatomical three‐dimensional imaging. Our objective was to determine if fish can be viable replacement animals in cancer studies using this technique by analysing the similarities between fish and humans in glucose uptake in select organs across multiple fish species. Rapid, quantifiable glucose uptake was demonstrated, particularly in brain, kidneys and liver in all imaged fish species. Standard uptake values for glucose uptake in the major organ systems of fish were more similar to those of humans than mice or dogs, indicating that fish may serve as effective alternative animal models using this technology. Applications for this technique in fish may include oncogenesis and metabolism studies as well as screening for environmental carcinogenesis.

Individual Intake of Free-Choice Mineral Mix by Grazing Beef Cows May Be Less Than Typical Formulation Assumptions and Form of Selenium in Mineral Mix Affects Blood Se Concentrations of Cows and Their Suckling Calves - Jennifer D. Patterson; Walter R. Burris; James A. Boling; James C. Matthews (Biological Trace Element Research, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Conserving large carnivores: dollars and fence - C. Packer; A. Loveridge; S. Canney; T. Caro; S.T. Garnett; M. Pfeifer; K.K. Zander; A. Swanson; D. MacNulty; G. Balme; H. Bauer; C.M. Begg; et al. (Ecology Letters, 2013)
Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced reserves can maintain lions at 80% of their potential densities on annual management budgets of $500 km −2 , unfenced populations require budgets in excess of $2000 km −2 to attain half their potential densities. Lions in fenced reserves are primarily limited by density dependence, but lions in unfenced reserves are highly sensitive to human population densities in surrounding communities, and unfenced populations are frequently subjected to density‐independent factors. Nearly half the unfenced lion populations may decline to near extinction over the next 20–40 years.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Effects of body mass and water temperature on routine metabolism of American paddlefish Polyodon spathula - J. T. Patterson; S. D. Mims; R. A. Wright (Journal of Fish Biology, 2013)
This study quantified the effects of temperature and fish mass on routine metabolism of the American paddlefish Polyodon spathula . Thermal sensitivity, as measured by Q 10 value, was low in P. spathula . Mean Q 10 was 1·78 while poikilotherms are generally expected to have Q 10 values in the 2·00–2·50 range. Mass‐specific metabolism did not decrease with increased fish size to the extent that this phenomenon is observed in teleosts, as evidenced by a mass exponent ( β ) value of 0·92 for P. spathula compared with 0·79 in a review of teleost species. Other Acipenseriformes have exhibited relatively high β values for mass‐specific respiration. Overall P. spathula metabolism appears to be more dependent on body mass and less dependent on temperature than for many other fishes. An equation utilizing temperature and fish mass to estimate gross respiration for P. spathula was derived and this equation was applied to respiratory data from other Acipenseriformes to assess inter‐species variation. Polyodon spathula respiration rates across water temperature and fish mass appear most similar to those of Atlantic sturgeon Acipenser naccarii and white sturgeon Acipenser transmontanus .

The physiological consequences of catch‐and‐release angling: perspectives on experimental design, interpretation, extrapolation and relevance to stakeholders - S. J. Cooke; M. R. Donaldson; C. M. O'connor; G. D. Raby; R. Arlinghaus; A. J. Danylchuk; K. C. Hanson; S. G. Hinch; T. D. Clark; D. A. Patterson; C. D. Suski (Fisheries Management and Ecology, 2013)
Over the past 20 years, there has been a dramatic increase in the use of physiological tools and experimental approaches for the study of the biological consequences of catch‐and‐release angling practices for fishes. Beyond simply documenting problems, physiological data are also being used to test and refine different strategies for handling fish such that stress is minimised and survival probability maximised, and in some cases, even for assessing and facilitating recovery post‐release. The inherent sensitivity of physiological processes means that nearly every study conducted has found some level of – unavoidable – physiological disturbance arising from recreational capture and subsequent release. An underlying tenet of catch‐and‐release studies that incorporate physiological tools is that a link exists between physiological status and fitness. In reality, finding such relationships has been elusive, with further extensions of individual‐level impacts to fish populations even more dubious. A focus of this article is to describe some of the challenges related to experimental design and interpretation that arise when using physiological tools for the study of the biological consequences of catch‐and‐release angling. Means of overcoming these challenges and the extrapolation of physiological data from individuals to the population level are discussed. The argument is presented that even if it is difficult to demonstrate strong links to mortality or other fitness measures, let alone population‐level impacts of catch‐and‐release, there remains merit in using physiological tools as objective indicators of fish welfare, which is an increasing concern in recreational fisheries. The overarching objective of this paper is to provide a balanced critique of the use of physiological approaches in catch‐and‐release science and of their role in providing meaningful information for anglers and managers.

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Spatial genetic and morphologic structure of wolves and coyotes in relation to environmental heterogeneity in a C anis hybrid zone - John F. Benson; Brent R. Patterson; Tyler J. Wheeldon (Molecular Ecology, 2012)
Eastern wolves have hybridized extensively with coyotes and gray wolves and are listed as a ‘species of special concern’ in C anada. However, a distinct population of eastern wolves has been identified in A lgonquin P rovincial P ark ( APP ) in O ntario. Previous studies of the diverse C anis hybrid zone adjacent to APP have not linked genetic analysis with field data to investigate genotype‐specific morphology or determine how resident animals of different ancestry are distributed across the landscape in relation to heterogeneous environmental conditions. Accordingly, we studied resident wolves and coyotes in and adjacent to APP to identify distinct C anis types, clarify the extent of the APP eastern wolf population beyond the park boundaries and investigate fine‐scale spatial genetic structure and landscape–genotype associations in the hybrid zone. We documented three genetically distinct C anis types within the APP region that also differed morphologically, corresponding to putative gray wolves, eastern wolves and coyotes. We also documented a substantial number of hybrid individuals (36%) that were admixed between 2 or 3 of the C anis types. Breeding eastern wolves were less common outside of APP , but occurred in some unprotected areas where they were sympatric with a diverse combination of coyotes, gray wolves and hybrids. We found significant spatial genetic structure and identified a steep cline extending west from APP where the dominant genotype shifted abruptly from eastern wolves to coyotes and hybrids. The genotypic pattern to the south and northwest was a more complex mosaic of alternating genotypes. We modelled genetic ancestry in response to prey availability and human disturbance and found that individuals with greater wolf ancestry occupied areas of higher moose density and fewer roads. Our results clarify the structure of the C anis hybrid zone adjacent to APP and provide unique insight into environmental conditions influencing hybridization dynamics between wolves and coyotes.

Process length variation of the cyst of the dinoflagellate Protoceratium reticulatum in the North Pacific and Baltic‐Skagerrak region: calibration as an annual density proxy and first evidence of pseudo‐cryptic speciation - Kenneth Neil Mertens; Manuel Bringué; Nicolas Van Nieuwenhove; Yoshihito Takano; Vera Pospelova; Andre Rochon; Anne De Vernal; Taoufik Radi; Barrie Dale; R. Timothy Patterson; Kaarina Weckström; Elinor Andrén; et al. (Journal of Quaternary Science, 2012)
Process length variation of cysts of the dinoflagellate Protoceratium reticulatum (Claparède et Lachmann) Bütschli in surface sediments from the North Pacific was investigated. The average process length showed a significant inverse relation to annual seawater density: σ t annual = −0.8674 × average process length + 1029.3 ( R 2 = 0.84), with a standard error of 0.78 kg m −3 . A sediment trap study from Effingham Inlet in British Columbia revealed the same relationship between average process length and local seawater density variations. In the Baltic–Skagerrak region, the average process length variation was related significantly to annual seawater density: σ t annual = 3.5457 × average process length − 993.28 ( R 2 = 0.86), with a standard error of 3.09 kg m −3 . These calibrations cannot be reconciled, which accentuates the regional character of the calibrations. This can be related to variations in molecular data (small subunit, long subunit and internal transcribed spacer sequences), which show the presence of several genotypes and the occurrence of pseudo‐cryptic speciation within this species. Copyright © 2012 John Wiley & Sons, Ltd.

Vertebrate metacommunity structure along an extensive elevational gradient in the tropics: a comparison of bats, rodents and birds - Steven J. Presley; Laura M. Cisneros; Bruce D. Patterson; Michael R. Willig (Global Ecology and Biogeography, 2012)
Aim We evaluated the structure of metacommunities for each of three vertebrate orders (Chiroptera, Rodentia and Passeriformes) along an extensive elevational gradient. Using elevation as a proxy for variation in abiotic characteristics and the known elevational distributions of habitat types, we assessed the extent to which variation in those factors may structure each metacommunity based on taxon‐specific characteristics. Location Manu Biosphere Reserve in the Peruvian Andes. Methods Metacommunity structure is an emergent property of a set of species distributions across geographic or environmental gradients. We analysed elements of metacommunity structure (coherence, range turnover and range boundary clumping) to determine the best‐fit structure for each metacommunity along an elevational gradient comprising 13 250‐m elevational intervals and 58 species of rodent, 92 species of bat or 586 species of passerine. Results For each taxon, the environmental gradient along which the metacommunity was structured was highly correlated with elevation. Clementsian structure (i.e. groups of species replacing other such groups along the gradient) characterized rodents, with a group of species that was characteristic of rain forests and a group of species that was characteristic of higher elevation habitats (i.e. above 1500 m). Distributions of bats were strongly nested, with more montane communities comprising subsets of species at lower elevations. The structure of the passerine metacommunity was complex and most consistent with a quasi‐Clementsian structure. Main conclusions Each metacommunity exhibited a different structure along the same elevational gradient, and each structure can be accounted for by taxon‐specific responses to local environmental factors that vary predictably with elevation. The structures of rodent and bird metacommunities suggest species sorting associated with habitat specializations, whereas structure of the bat metacommunity is probably moulded by a combination of species‐specific tolerances to increasingly cold, low‐productivity environs of higher elevations and the diversity and abundance of food resources associated with particular habitat types.

The complimentary role of genetic and ecological data in understanding population structure: a case study using moose (Alces alces) - L. A. Finnegan; P. J. Wilson; G. N. Price; S. J. Lowe; B. R. Patterson; M.-J. Fortin; D. L. Murray (European Journal of Wildlife Research, 2012)

Non-steroidal anti-inflammatory drugs and cancer incidence by sex in the VITamins And Lifestyle (VITAL) cohort - Theodore M. Brasky; John D. Potter; Alan R. Kristal; Ruth E. Patterson; Ulrike Peters; Maryam M. Asgari; Mark D. Thornquist; Emily White (Cancer Causes & Control, 2012)

Canine epilepsy genetics - Kari J. Ekenstedt; Edward E. Patterson; James R. Mickelson (Mammalian Genome, 2012)

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

A sledge microtome for high resolution subsampling of freeze cores - Andrew L. Macumber; R. Timothy Patterson; Lisa A. Neville; Hendrik Falck (Journal of Paleolimnology, 2011)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A new high-latitude record for the macaroni penguin (Eudyptes chrysolophus) at Avian Island, Antarctica - K. B. Gorman; E. S. Erdmann; B. C. Pickering; P. J. Horne; J. R. Blum; H. M. Lucas; D. L. Patterson-Fraser; W. R. Fraser (Polar Biology, 2010)

Controls on the contemporary distribution of lake thecamoebians (testate amoebae) within the Greater Toronto Area and their potential as water quality indicators - Helen M. Roe; R. Timothy Patterson; Graeme T. Swindles (Journal of Paleolimnology, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Climate simulations of major estuarine watersheds in the Mid-Atlantic region of the US - R. Najjar; L. Patterson; S. Graham (Climatic Change, 2009)

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Cold shock and fish - M. R. Donaldson; S. J. Cooke; D. A. Patterson; J. S. Macdonald (Journal of Fish Biology, 2008)
Rapid decreases in water temperature may result in a number of physiological, behavioural and fitness consequences for fishes termed ‘cold shock’. Cold‐shock stress occurs when a fish has been acclimated to a specific water temperature or range of temperatures and is subsequently exposed to a rapid decrease in temperature, resulting in a cascade of physiological and behavioural responses and, in some cases, death. Rapid temperature decreases may occur from either natural ( e.g. thermocline temperature variation, seiches and storm events) or anthropogenic sources ( e.g. varied thermal effluents from power generation and production industries). The magnitude, duration and frequency of the temperature change as well as the initial acclimation temperatures of individuals can influence the extent of the consequences of cold shock on fishes. Early research on cold shock focused on documenting mortality events associated with cold shock. However, in recent years, a shift in research has occurred where the focus of cold‐shock studies now involves characterizing the sublethal effects of cold shock in terms of the stress response in fishes. This shift has revealed that cold shock can actually be used as a tool for fisheries science ( e.g. to induce polyploidy). The cold‐shock stress response offers opportunities to develop many exciting research questions, yet to date, cold‐shock research has been largely unfocused. Few studies attempt to link laboratory physiology experiments with ecologically relevant field data on behaviour, growth, bioenergetics and fitness. Additional research will allow for the development of more focused and robust management policies and conservation initiatives. This review synthesizes the sublethal physiological and behavioural consequences of cold‐shock stress on fishes, identifies natural and anthropogenic sources of cold shock, discusses the benefits of cold shock to fisheries science and describes mitigation and management efforts. Existing knowledge gaps and opportunities for future cold‐shock research are presented.

The effects of prey demography on humpback whale (Megaptera novaeangliae) abundance around Anvers Island, Antarctica - Ari S. Friedlaender; William R. Fraser; Donna Patterson; Song S. Qian; Patrick N. Halpin (Polar Biology, 2008)

The conspecific nature of eastern and red wolves: conservation and management implications - C. J. Kyle; A. R. Johnson; B. R. Patterson; P. J. Wilson; B. N. White (Conservation Genetics, 2008)

Optimal Crop Rotation of Idaho Potatoes - Penny Myers; Christopher S. McIntosh; Paul E. Patterson; R. Garth Taylor; Bryan G. Hopkins (American Journal of Potato Research, 2008)

Diatoms and pollen as indicators of water quality and land-use change: a case study from the Oak Ridges Moraine, Southern Ontario, Canada - Melissa A. Watchorn; Paul B. Hamilton; Thane W. Anderson; Helen M. Roe; R. Timothy Patterson (Journal of Paleolimnology, 2008)

Cutaneous and diphtheritic avian poxvirus infection in a nestling Southern Giant Petrel (Macronectes giganteus) from Antarctica - Valerie Shearn-Bochsler; D. Earl Green; Kathryn A. Converse; Douglas E. Docherty; Teresa Thiel; Heidi N. Geisz; William R. Fraser; Donna L. Patterson-Fraser (Polar Biology, 2008)

Vitamin E and selenium supplementation and risk of prostate cancer in the Vitamins and lifestyle (VITAL) study cohort - Ulrike Peters; Alyson J. Littman; Alan R. Kristal; Ruth E. Patterson; John D. Potter; Emily White (Cancer Causes & Control, 2008)

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

Impact of the 2005 coral bleaching event on Porites porites and Colpophyllia natans at Tektite Reef, US Virgin Islands - K. R. T. Whelan; J. Miller; O. Sanchez; M. Patterson (Coral Reefs, 2007)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Long-term Evaluation of a Composite Cover Overlaying a Sulfidic Tailings Facility - B. M. Patterson; B. S. Robertson; R. J. Woodbury; B. Talbot; G. B. Davis (Mine Water and the Environment, 2006)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Genomics of plant cell wall biogenesis - Weidong Yong; Bruce Link; Ronan O’Malley; Jagdish Tewari; Charles T. Hunter; Chung-An Lu; Xuemei Li; Anthony B. Bleecker; Karen E. Koch; Maureen C. McCann; Donald R. McCarty; Sara E. Patterson; et al. (Planta, 2005)

A paleolimnological record of Holocene climate and environmental change in the Temagami region, northeastern Ontario - Robert E. A. Boudreau; Jennifer M. Galloway; R. Timothy Patterson; Arun Kumar; Frederick A. Michel (Journal of Paleolimnology, 2005)

Molecular genetic variation across the southern and eastern geographic ranges of the African lion, Panthera leo - Jean Dubach; B. D. Patterson; M. B. Briggs; K. Venzke; J. Flamand; P. Stander; L. Scheepers; R. W. Kays (Conservation Genetics, 2005)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Population structure of red drum ( Sciaenops ocellatus ) as determined by otolith chemistry - H. M. Patterson; N. Julien; R. S. McBride (Marine Biology, 2004)

Measurement of Toxaphene Congeners in Pooled Human Serum Collected in Three U.S. Cities Using High-Resolution Mass Spectrometry - John R. Barr; Adrian R. Woolfitt; Vincent L. Maggio; Donald G. Patterson (Archives of Environmental Contamination and Toxicology, 2004)

VARIABILITY IN THE DIET OF HARBOR PORPOISES ( PHOCOENA PHOCOENA ) IN SCOTTISH WATERS 1992–2003 - M. B. Santos; G. J. Pierce; J. A. Learmonth; R. J. Reid; H. M. Ross; I. A. P. Patterson; D. G. Reid; D. Beare (Marine Mammal Science, 2004)
A bstract Interannual, seasonal, and regional variation in the diet of porpoises, Phocoena phocoena , in Scottish (UK) waters was studied using stomach contents of animals stranded between 1992 and 2003. Most samples came from the east coast (including many porpoises killed by bottlenose dolphins), with smaller numbers from the west coast and from Shetland. The most important prey types, in terms of contribution by number and mass, were whiting ( Merlangius merlangus ) and sand eels (Ammodytidae). Multivariate analysis confirmed the existence of regional, seasonal, and interannual variation in diet, as well as differences ( i. e. , biases) related to cause of death. These differences were further explored using univariate analyses. Sand eels were more important in the summer months (quarters 2 and 3) and on the east coast, whereas gadids were more important in winter and in the Shetland area. Some, but not all, observed trends in the numerical importance and size of prey taken were consistent with trends in abundance and size of fish taken during research trawl surveys. There was some evidence that porpoises Clupea harengus and sprat Sprattus sprattus ) formed a relatively small proportion of the diet, but their importance varied from year to year. Although possible methodological biases prevent firm conclusions, it appears that the importance of clupeids in porpoise diet may have decreased since the 1960s, mirroring the decline in North Sea herring abundance. The recovery of the North Sea herring stock in recent years is not as yet reflected in porpoise diet.

Impedance cardiographic measurement of the physiological response to the Valsalva manoeuvre - R. P. Patterson; J. Zhang (Medical & Biological Engineering & Computing, 2003)

Effects of Dietary Exposure to Environmentally Relevant Concentrations of Weathered Prudhoe Bay Crude Oil in Ranch-Raised Mink ( Mustela vison ) - K. J. Beckett; R. J. Aulerich; L. K. Duffy; J. S. Patterson; S. J. Bursian (Bulletin of Environmental Contamination and Toxicology, 2002)

Arcellaceans (thecamoebians) as indicators of land-use change: settlement history of the Swan Lake area, Ontario as a case study - R. Timothy Patterson; Andrew Dalby; Arun Kumar; Lori A. Henderson; Robert E.A. Boudreau (Journal of Paleolimnology, 2002)

Variation at high latitudes: the geography of body size and cranial morphology of the muskox, Ovibos moschatus - Paul A. Smith; James A. Schaefer; Brent. R. Patterson (Journal of Biogeography, 2002)
Aim Bergmann's rule, one of the most studied and controversial ecogeographical generalizations, has rarely been tested with observations from high latitudes. We tested the rule using cranial measurements of the muskox [ Ovibos moschatus (Zimmerman)], a homeotherm with an extremely northern distribution. We also used these data to describe geographical patterns in the species' dental architecture, an extension of the framework developed from interspecific comparisons. Location Specimens were compiled from arctic Canada, Alaska and Greenland, a latitudinal range of 60° N−83° N. Methods Body size was estimated from principal components analysis (PCA) of five cranial characters from 128 specimens. Mean scores on the first principal component from each locality were regressed against latitude and mean temperature to identify geographical variation in body size; scores on the second principal component were regressed against latitude to assess patterns in dental architecture. Regression analyses of the individual characters were performed as a complement to PCA. Results No latitudinal or climatic trend in body size was observed in either sex. On the other hand, for males, significant latitudinal variation was found for the second PCA axis ( r = −0.434), and the feature which loaded most heavily on it, maxillary tooth row length ( r = 0.429). For females, this dental structure also tended to increase with latitude ( r = 0.423), but the trend was only marginally significant ( P =0.12), perhaps owing to a smaller sample size. Main conclusions The geographically invariant body size of muskoxen failed to support current hypotheses of size variation. Behavioural and physiological adaptations may exempt the muskox from selective pressures underlying these hypotheses. We interpret latitudinal variation in dental architecture as a reflection of a cline in diet, dominated by graminoids at the expense of willows at higher latitudes. This intraspecific geographical trend is a recapitulation of the interspecific framework for large mammalian herbivores.

Prevalence of a Novel Capsule-Associated Lipoprotein Among Pasteurellaceae Pathogenic in Animals - Franklin R. Champlin; Thomas R. Shryock; Charles E. Patterson; Frank W. Austin; Phillip E. Ryals (Current Microbiology, 2002)

Contributions of forage competition, harvest, and climate fluctuation to changes in population growth of northern white-tailed deer - Brent R. Patterson; Vince A. Power (Oecologia, 2002)

Plasticity in water-use efficiency of Picea sitchensis, P. glauca and their natural hybrids - S. Silim; R. Guy; T. Patterson; N. Livingston (Oecologia, 2001)

A comparison of methods for detection of phosphate limitation in microalgae - John Beardall; Tom Berman; Phil Heraud; Medina Omo Kadiri; Brett R. Light; Graeme Patterson; Simon Roberts; Barbara Sulzberger; Emel Sahan; Urs Uehlinger; Bayden Wood (Aquatic Sciences, 2001)

Angiotensin II induces gene transcription through cell-type-dependent effects on the nuclear factor-κB (NF-κB) transcription factor - Allan R. Brasier; M. Jamaluddin; Youqui Han; Cam Patterson; Marschall S. Runge (Molecular and Cellular Biochemistry, 2000)

The Diagnosis and Recommendation Integrated System (DRIS) for diagnosing the nutrient status of grassland swards: III Practical applications - J. S. Bailey; R. A. Dils; R. H. Foy; D. Patterson (Plant and Soil, 2000)

Analysis of otolith chemistry in Nassau grouper ( Epinephelus striatus ) from the Bahamas and Belize using solution-based ICP-MS - H. M. Patterson; S. R. Thorrold; J.M. Shenker (Coral Reefs, 1999)

A Historical Perspective on Pitch PineScrub Oak Communities in the Connecticut Valley of Massachusetts - G. Motzkin; W. A. Patterson III; D. R. Foster (Ecosystems, 1999)

Assessment of a Sr isotope vital effect (87Sr/86Sr) in marine taxa from Lee Stocking Island, Bahamas - E. G. Reinhardt; J. Blenkinsop; R. T. Patterson (Geo-Marine Letters, 1998)

Substrate use during and following moderate- and low-intensity exercise: Implications for weight control - D. L. Thompson; K. M. Townsend; R. Boughey; K. Patterson; D. R. Bassett Jr (European Journal of Applied Physiology, 1998)

Vitamin supplements and cancer risk: the epidemiologic evidence - R. E. Patterson; E. White; A. R. Kristal; M. L. Neuhouser; J. D. Potter (Cancer Causes & Control, 1997)

Evidence for rapid avian-mediated foraminiferal colonization of Lake Winnipegosis, Manitoba, during the Holocene Hypsithermal - R. Timothy Patterson; W. Brian McKillop; Sid Kroker; Erik Nielsen; Eduard G. Reinhardt (Journal of Paleolimnology, 1997)

Whole-plant nitrogen- and water-relations traits, and their associated trade-offs, in adjacent muskeg and upland boreal spruce species - T. B. Patterson; R. D. Guy; Q. L. Dang (Oecologia, 1997)

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 1. Insitu pumping rates - Mark R. Patterson; Valeri I. Chernykh; Vladimir A. Fialkov; Michael Savarese (Limnology and Oceanography, 1997)
Demosponges dominate the littoral zone of Lake Baikal, Russia. During August 1993, we measured the in situ pumping activity of a globose sponge, Baikalospongia bacillifera, common at depths of 8–50 m. Excurrent flow speed, surface area, and oscular diameter were measured with fluorescein dye release, underwater video, and image processing for nine individual sponges; diel deployments of a heated thermistor flowmeter were made on another three individuals. Mean pumping rates for oscula ranged from 0.2 to 3.3 cm s −1 , with instantaneous measurements as high as 25 cm s −1 . Although between‐sponge variability is large, oscula from an individual maintain speeds within 1 cm s −1 of each other. Volume fluxes for oscula measured from all individuals range from 0.01 to 0.60 cm 3 s −1 . Fluxes for individuals indicate that a sponge processes its volume in 17–24 s, comparable to values obtained for marine species. Oscula are not continuously active and often reduce pumping for several hours at irregular intervals. Two of three individuals monitored over a diel cycle exhibited negative correlations between the ambient current and oscular excurrent flow. Boundary layer measurements and diffusivity calculations demonstrate that sponges are capable of depleting picoplankton near the bottom.

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 2. Sponge abundance, diet, feeding efficiency, and carbon flux - Adele J. Pile; Mark R. Patterson; Michael Savarese; Valeri I. Chernykh; Vladimir A. Fialkov (Limnology and Oceanography, 1997)
Endemic freshwater demosponges in the littoral zone of Lake Baikal, Russia, dominate the benthic biomass, covering 44% of the benthos. We measured in situ sponge abundance and grazing and calculated sponge‐mediated fluxes of picoplankton (plankton µ m) for two common species, Baikalospongia intermedia and Baikalospongia bacillifera. By means of dual‐beam flow cytometry, we found retention efficiencies ranging from 58 to 99% for four types of picoplankton: heterotrophic bacteria, Synechococcus‐type cyanobacteria, autotrophic picoplankton with one chloroplast, and autotrophic picoplankton with two chloroplasts. By using a general model for organism‐mediated fluxes, we conservatively estimate that through active suspension feeding, sponges are a sink for 1.97 g C d −1 m −2 , mostly from procaryotic cell types. Furthermore, grazing by these extensive sponge communities can create a layer of picoplankton‐depleted water overlying the benthic community in this unique lake.

Simulation of the effect of methane bubble plumes on vertical mixing in Mono Lake - Jos R. Romero; John C. Patterson; John M. Melack (Aquatic Sciences, 1996)

Location and geometric description of carpal bones in CT images - H. D. Tagare; K. W. Elder; D. M. Stoner; R. M. Patterson; C. L. Nicodemus; S. F. Viegas; G. R. Hillman (Annals of Biomedical Engineering, 1993)

Mouse hepatitis virus strain 3 infection of C57, A/Sn and A/J strain mice and their macrophages - M. R. Macnaughton; S. Patterson (Archives of Virology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Electron microscope observations on the entry of avian infectious bronchitis virus into susceptible cells - S. Patterson; R. W. Bingham (Archives of Virology, 1976)

Evaluation of phorate and Di-Syston for potato insect control in New York - R. S. Patterson; W. A. Rawlins (American Journal of Potato Research, 1964)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)